Existence and uniqueness of solutions for a singular system of higher-order nonlinear fractional differential equations with integral boundary conditions - Wang, Lin; Zhang, Xingqiu; Lu, Xinyi (Nonlinear Analysis: Modelling and Control, 2013)
In this paper, we study the existence and uniqueness of solutions for a singular system of nonlinear fractional differential equations with integral boundary conditions. We obtain existence and uniqueness results of solutions by using the properties of the Green’s function, a nonlinear alternative of Leray–Schauder-type, Guo–Krasnoselskii’s fixed point theorem in a cone and the Banach fixed point theorem. Some examples are included to show the applicability of our results.